Energy-Efficient Compact Heat Exchangers Made of Porous Heat-Conducting Materials - S. N. Osipov; A. V. Zakharenko (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика)
After successful increase of levels of thermal resistances of building enclosing structures, expenses of heat on ventilation of rooms in many cases reached similar magnitudes of indicators of heating in a cold season. Therefore, the development of new efficient heat exchangersheat exchangers of small size is of particular importance. It is possible now to create highperformance thin (of a few centimeters) heat exchangers of such high-porous heat-conducting materials as copper, aluminum, etc. Highly porous materials include porous-permeable structures having an open porosity (with a total pore surface area of more than 50 % in relation to a smooth surface). One of the main conditions for the qualitative use of such high-porous thermal conductive materials is the rapid removal of condensate outside the heat exchange zone without a significant increase in filtration resistance. Thermal calculation of such heat exchangers is based on the criteria of Fourier (Fu) and Predvoditelev (Рd). Various ways of using high-porous heat-conducting materials in the design of heat exchangers are considered. The method of production of the heat exchanger based on the application of porous-permeable material in the channels of the heat exchange part of recuperative devices is presented; the difference of the method is that the heat exchange part is performed of two or more parallel heat exchange plates with spacing between them. It has been found that a significant increase in the energy efficiency of heat exchangers of this type is possible due to the application of even small discontinuities of the heat-conducting layers of high-porous materials so to use the specific features of increased heat exchange of the initial sections with the flowing fluid. One of the main advantages of using air-to-air heat exchangers made of foamed high-heat-conducting material in the climatic conditions of Belarus is freezing resistance.